Para a construção de um glossário na obra sousandradina : uma contribuição - Godoi, Eliamar (2007)
This research had as objective to make a glossary with the neologisms created by Sousândrade in the literary works: Harpas Selvagens (1857) and Harpa de Ouro (1888 / 1889) and to create definitions for the neological words based on the context of these works. To develop this work, the chosen methodological procedure was of the bibliographical research that involved important theories for the development of this dissertation. In this way, based on the foundations of Boulanger s theory (1979), 124 neológicals units were listed and analyzed, between formal and semantic neologism. As theoretical base, were used, also, the concepts formulated by linguists such as Guilbert (1975), Rey (1976), Barbosa (1981; 2000) and Sablayrolles (1996). The work hypotheses have been confirmed, therefore, were verified that, really, the sousandradino´s vocabulary contains formal and semantic neologisms and there was a bigger appearance of neologisms, above all, that ones formed by composition, in the last works produced by the author. Still, in elapsing of the research, it could be evidenced that the author lets show himself for his lexicon, because, he manifests his experiences and ideologies trough an autobiographical work. Thus, points of view and parts of the reality, of the time lived by him, come evident in his lexical creations. Among the mechanisms of word formation used, the composition process was the one that called more attention to the unusual creations and synthetism used by Sousândrade, although derivation process was also used. In all cases, it was necessary to appeal to the linguistic and extra linguistic context, to understand the sense of the neological words. Nevertheless be a partial analysis, expects that this work contributes of significant form for the growth of the linguistic studies, above all, that ones in that refers to the studies about the lexicon of this author. It is expected, still, that this research be a form of to became perennial the lexicon of Sousândrade and also of better understanding the work and the sociologic-historical-cultural moment in which was processed his language and creativity.